2021
DOI: 10.1002/jnr.24795
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of brain structural networks in aging: A longitudinal study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 141 publications
(194 reference statements)
4
19
0
Order By: Relevance
“…These results corroborate previous findings of age effects in multiple indicators of WM microstructure, including WM integrity (e.g., Sexton et al, 2014), WM fiber density (Choy et al, 2020), and number of streamline counts (Coelho et al, 2021). Together with the present results, these findings indicate robust and replicable effects of age on WM microstructure across measurements and using different biophysical models of water diffusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results corroborate previous findings of age effects in multiple indicators of WM microstructure, including WM integrity (e.g., Sexton et al, 2014), WM fiber density (Choy et al, 2020), and number of streamline counts (Coelho et al, 2021). Together with the present results, these findings indicate robust and replicable effects of age on WM microstructure across measurements and using different biophysical models of water diffusion.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of lower structural connectivity strength in older compared to younger adults also support previous computational work showing that the degree to which structural brain networks rely on geometric wiring rules is weakened with advancing age (Betzel et al, 2016; Zuo et al, 2017). This finding may also indicate less structural constraints on functional brain organization with advancing age, which might lead to disassociation of the topographical organizations between structural and function connectivity in older adults (Coelho et al, 2021; Zamani Esfahlani et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Distant and local interconnections exist between different brain regions, forming brain networks ( 52 , 53 ). To our knowledge, changes in regional synchronization and functional connectivity patterns in HIV-associated asymptomatic cognitive impairment have not been simultaneously investigated in previous rs-fMRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between structural/functional networks and cognitive functions over 2 years (cognitive test ~ node connectivity + time + pseudo + age + sex + education) ventional studies have revealed that reorganization of brain structure (Coelho et al, 2021;Fjell et al, 2017;Hirsiger et al, 2016) and function (Bagarinao et al, 2019;Malagurski et al, 2020;Stumme et al, 2020) in advanced aging provides a compensatory mechanism to enhance, maintain, or reconfigure cognition over time. Hubs, which involve superior connections with the rest of the brain, maintain the optimal information segregation and integration balance that maximizes the communication efficiency by long range connections and minimizes the wiring cost (Bullmore & Sporns, 2009).…”
Section: Ta B L Ementioning
confidence: 99%